2011
DOI: 10.1063/1.3590336
|View full text |Cite
|
Sign up to set email alerts
|

A cylindrical optical black hole using graded index photonic crystals

Abstract: The electromagnetic wave propagation of a two-dimensional optical black hole with graded index photonic crystals for transverse magnetic modes is studied. The implementation of the proposed system is validated in the metamaterial regime. The finite element method is employed in order to confirm the optical properties of the designed device. Numerical simulations show that the light incident on the device is bent toward the central area and absorbed by the inner core. As a result, the artificial optical black h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Inspired by nature, optical properties of spiral structures have been explored in many aspects, for instances, photonic crystal fibers (PCF) [1], nanoplasmonic spirals [2] etc.. Recently, Gradient index structures [3] have received increased attention in the recent literature from invisibility cloak [4,5] and optical black hole [6], to planar devices such as Luneberg lens [7,8]. Generally, GRIN materials required continuous graded index profile.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, optical properties of spiral structures have been explored in many aspects, for instances, photonic crystal fibers (PCF) [1], nanoplasmonic spirals [2] etc.. Recently, Gradient index structures [3] have received increased attention in the recent literature from invisibility cloak [4,5] and optical black hole [6], to planar devices such as Luneberg lens [7,8]. Generally, GRIN materials required continuous graded index profile.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, the broad range of photonic crystal (PC) applications enables the design of various cavities, waveguides, switches, mirrors and filters [3]. While they were also shown that the potential applications ranges from invisibility cloaks [4,5] and optical black holes [6], to planar devices such as Luneburg [7,8]. The graded photonic crystals (GPCs) consist of unit cells with spatially varying geometrical or material properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various stmctures were proposed as an absorber, including tubes [6], v-grooves [7], roughened surfaces [8], a moth-eye film on silicon [9], onedimensional (ID) grating on a film [10], two-dimensional (2D) grating on a film [11], corrugated surfaces [12], core-shell [13], 2D cylindrical [14] and square [15] photonic crystals, and multilayers [16]. The power throughput and energy conversion efficiency can be both low if the irradiation is reflected or re-emitted from the absorber surface.…”
Section: Introductionmentioning
confidence: 99%